PHOTOPHYSICAL AND PHYSICOCHEMICAL PROPERTIES OF Cu(II)CHLORIN e4 AND Cu(II)CHLORIN e6 AS A LEAD COMPOUND OF PHOTOSENSITIZER FOR PDT - Eva Susanty Simaremare; Asmiyenti D. Djalil; Daryono H. Tjahjono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Porphyrin derivatives are potential compounds for diagnostic agent and photosensitizer in photodynamic therapy. However, they have a weakness in molar absorptivity, especially in visible region of Q band which used to excite them. Due to incapabilities of porphyrin, other tetrapyrole derivatives, such as chlorophyllin can be alternative for a lead compound of photosensitizer. In the present research, two chlorin derivatives were isolated from commercial chlorophyllin product. Their photophysical and physicochemical properties, i.e. molar absorptivity, quantum yield of fluorescence and quantum yield of singlet oxygen were determined. Chlorophyllin carboxylic acid form, Cu(II)-chlorin e4 and Cu(II)-chlorin e6,were successfully isolated with recovery of 11.33% and 16.46%, respectively. The absorption spectrum of Cu(II)-chlorin e4 showed an intense Soret band at 406 nm and two weaker Q bands at 628nm, 658nm. Fluorescence efficiency was 0.09 while efficiency for singlet oxygen at pH 6.3 and 7.4 were 0.0052±0.0017 and 0.0066±0.0012. Cu(II)-chlorin e6 displayed soret band at 407nm and Q bands at 627nm, 663nm. Singlet oxygen at pH 6.3 was 0.0029±0.0007, while at pH 7.4 was 0.0034±0.0001. However, Cu(II)-chlorin e6 did not show fluorescence.Key words: Chlorophyllin, Cu(II)-chlorin e4, Cu(II)-chlorin e6, singlet oxygen fluorescence